Applying a biodeposition layer to increase the bond of a repair mortar on a mortar substrate. (February 2018) - Snoeck, D.; Wang, J.; Bentz, D.P.; De Belie, N.
Abstract: One of the major concerns in infrastructure repair is a sufficient bond between the substrate and the repair material, especially for the long-term performance and durability of the repaired structure. In this study, the bond of the repair material on the mortar substrate is promoted via the biodeposition of a calcium carbonate layer by a ureolytic bacterium. X-ray diffraction and scanning electron microscopy were used to examine the interfaces between the repair material and the substrate, as well as the polymorph of the deposited calcium carbonate. The approximately 50 μm thick biodeposition film on the mortar surface mostly consisted of calcite and vaterite. Both the repair material and the substrate tended to show a good adherence to that layer. The bond, as assessed by slant shear specimen testing, was improved by the presence of the biodeposition layer. A further increase was found when engineering the substrate surface using a structured pattern layer of biodeposition.